"Sequential multimodality stimulation" for post-stroke-hemineglect: Feasibility and outcome in a pilot randomized controlled trial. (January 2020) - Sukumaran, Sajith; Sivadasan, Sesh; Sakunthala, Parthan T.; Tandon, Vaibhav; Sarma, Sankara P.
Highlights: Encouraging results in this pilot RCT. Feasible and promising rehabilitation strategy for post-stroke hemineglect. Larger studies are warranted to prove the efficacy beyond doubt. If proven, major impact on the post-stroke rehabilitation. Abstract: Objective: To test the feasibility and efficacy of multimodality stimulation combined with motor tasking as a corrective strategy for hemineglect following right hemispheric ischemic strokes. Material and methods: A prospective randomized controlled single blinded clinical trial was conducted over eighteen months from January 2017. All patients with right hemispheric ischemic strokes were screened for hemineglect and those fulfilling criteria were recruited and randomized. Patients under the therapy group (TG) received the intervention based on a structured protocol in addition to standard physiotherapy. The control group (CG) received standard physiotherapy alone. NIHSS, mRS and Neuropsychological test scores were recorded at different time points. The primary outcome measures (neuropsychological test scores) were compared between the two groups (Student's t -test to find out the difference in outcome measures) at one and three months post-stroke. Results: Of the 14 patients recruited, data from 12 were available for analysis, 5 patients in TG and 7 in CG. There was a trend for better hemineglect and functional outcomes in TG. Conclusion: Multimodality stimulation, in addition to standard physiotherapy, is feasible and potentially results in better neurocognitive and functional recovery following right hemispheric ischemic strokes. However, larger studies are warranted to prove these preliminary observations beyond doubt.